2022
DOI: 10.3389/fnins.2022.898800
|View full text |Cite
|
Sign up to set email alerts
|

Typical and Atypical Development of Visual Expertise for Print as Indexed by the Visual Word N1 (N170w): A Systematic Review

Abstract: The visual word N1 (N170w) is an early brain ERP component that has been found to be a neurophysiological marker for print expertise, which is a prelexical requirement associated with reading development. To date, no other review has assimilated existing research on reading difficulties and atypical development of processes reflected in the N170w response. Hence, this systematic review synthesized results and evaluated neurophysiological and experimental procedures across different studies about visual print e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 118 publications
2
13
1
Order By: Relevance
“…The results showed that the main effect of recording year was not significant (F (1,531) = 0.332, p = 0.565), and the interaction of recording year with Age and Stimulus Type was not significant (F (4,531) = 1.966, p = 0.098; F (2,531) = 0.067, p = 0.935), and there was no interaction between the three factors (F (8,531) = 0.254, p = 0.980). The main effect of Age was significant (F (4,531) = 11.443, p < 0.001), which was consistent with previous studies that N1 decreased with children development (Amora et al, 2022). However, our results further showed that there was no significant difference in N1 amplitude between 2009 and 2019 recording group, suggesting that the basic visual processing development is similar between the two groups.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that the main effect of recording year was not significant (F (1,531) = 0.332, p = 0.565), and the interaction of recording year with Age and Stimulus Type was not significant (F (4,531) = 1.966, p = 0.098; F (2,531) = 0.067, p = 0.935), and there was no interaction between the three factors (F (8,531) = 0.254, p = 0.980). The main effect of Age was significant (F (4,531) = 11.443, p < 0.001), which was consistent with previous studies that N1 decreased with children development (Amora et al, 2022). However, our results further showed that there was no significant difference in N1 amplitude between 2009 and 2019 recording group, suggesting that the basic visual processing development is similar between the two groups.…”
Section: Resultssupporting
confidence: 92%
“…This is similar to the development curve of the visual N170 component associated with expertise for visual stimuli such as words. Longitudinal studies have shown an inverted U-shape development curve of the N170, with an increased response for orthographic stimuli in beginning readers followed by a slight decrease when readers become fluent ( Fraga-Gonzalez et al, 2021 ; Amora et al, 2022 ). Developmental data suggested an inverted U-shape trajectory of visual responses discriminating between words and symbols ( Maurer et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is similar to the previously identified occipitotemporal N170 component, which was interpreted as an earlier maker of visual-orthographic processes in visual word recognition (i.e., differentiates between orthographic stimuli other stimuli such as symbols and faces Carreiras et al (2014); Dehaene, Cohen, Sigman, and Vinckier (2005); Solomyak and Marantz (2009)). Studies focusing on the N170 component (see Amora et al, 2022; Pickering & Gambi, 2018 for a systematic review) also reported that N170 activity may correspond to logographic processing where a word is processed as a whole during the reading of very frequent words or after a massive repetition of a word (Simon, Petit, Bernard, & Rebäi, 2007). However, such findings are hardly found consistently across studies (Nieuwland, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier components have also been shown to be predictive of reading skills, such as the N170 response, which reflects experience with visual words. Reading expertise leads to left lateralization of the N170 response in both alphabetic and logographic scripts [31,32], driven by script familiarity. Children also have a different CNV response in rhyming tasks compared to adults, as the CNV amplitude lowers with age [20].…”
Section: Introductionmentioning
confidence: 98%